2012
DOI: 10.1002/pmic.201200208
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics of parotid saliva in primary Sjögren's syndrome

Abstract: The diagnosis of primary Sjögren’s syndrome (pSS) is difficult due to the lack of specific laboratory and clinical tests. As an initial step for the global discovery of changes in the abundance of parotid salivary proteins in pSS, a pooled sample was compared to that from healthy control (HC) subjects by multidimensional protein identification technology (MudPIT). A total of 1246 proteins were identified by MudPIT. The abundance of 477 of these proteins did not change, 529 were only detected in either the pSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 35 publications
0
28
0
1
Order By: Relevance
“…Similarly, previous proteomic studies on whole saliva have determined broad and distinct protein patterns that are characteristic of SS, including secretory proteins, enzymes, highly abundant immune system-related molecules (e.g. β2-microglobulin), and cytokines such as IL-4 and IL-5 [21, 28, 29]. The current STRING analysis of whole saliva also strengthens the concept of involvement and over-activation of the innate and adaptive immune system in SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, previous proteomic studies on whole saliva have determined broad and distinct protein patterns that are characteristic of SS, including secretory proteins, enzymes, highly abundant immune system-related molecules (e.g. β2-microglobulin), and cytokines such as IL-4 and IL-5 [21, 28, 29]. The current STRING analysis of whole saliva also strengthens the concept of involvement and over-activation of the innate and adaptive immune system in SS.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, several common biomarkers for SS have been found, including secretory proteins, enzymes, highly abundant immune-system-related molecules (e.g. β2-microglobulin), and cytokines such as IL-4 and IL-5 [21, 28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…Proteomic technologies are currently being used to discover disease biomarkers, particularly for oral cancer [25,26], lung disease [27], Sjögren's syndrome [28,29], and gingivitis [30].…”
Section: Salivary Proteome and Diagnosismentioning
confidence: 99%
“…In search of SS-specific biomarkers, investigators have studied saliva and tears from SS patients and mouse models. Quantitative proteomic study of parotid saliva identified 529 proteins specific to either primary SS patients or healthy controls, including many proteins with immunologic functions [20]. In tear fluid, immune cell mRNA was detected in autoimmune dacryoadenitis prone mice [21].…”
Section: Pathogenesismentioning
confidence: 99%